HISTOLOGICAL CHANGES IN ORAL MUCOSA INDUCED BY TOBACCO USE: A COMPARATIVE STUDY IN PESHAWAR - Dr Zahir Dad Khan; Dr Talha Maqbool; Dr Azeem Murad Ali; Dr Pashmina Nisar; Dr Tanzeela; Dr Jamal Nasir Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction Smoked and smokeless tobacco consumption is a major factor that leads to pathological alterations in oral mucosa: leukoplakia and oral sub mucous fibrosis. Most of these changes are known to predispose an individual to oral cancer. This study was designed to evaluate differences in the pathological changes in the oral tissues of tobacco users and non-users in the context of the city of Peshawar, with a view to examining the severity of tobacco effects. Methodology An observational analytical study of Tobacco user and Non-Tobacco users was carried out, in Khyber Medical University, Peshawar using cross-sectional comparative study in which, 100 participant included 50 Tobacco users & 50 Non Tobacco users participated between January to June 2024. In this study, oral mucosal biopsy samples were taken from the patients and the following histopathological changes were evaluated; epithelial thickness, keratinization, degree of dysplasia and degree of inflammatory infiltration. Descriptive analysis was done using chi-square test at 0.05 level of signification. Results There was also a statistically significant difference between the control groups. In group 1 hyperkeratosis was observed in 80% of participants and mild to moderate changes of dysplasia in 25% of participants and 70% of participants with inflammatory infiltrates. The prevalence of sub epithelial fibrosis was 15% among tobacco users. Group 2 (non–user) had no dysplasia even though the degree of inflammation was minimal. Conclusion Tobacco has well defined relationship with histologic alterations of the cells within oral mucosal surface that is characterized by hyperkeratosis, dysplasia and chronic inflammation. Therefore this result support the practice of performing dental check at regular intervals for those practicing any form of tobacco use and declares that further work needs to be done in the crusade to minimize people’s use of tobacco products.